Light-Activated Sub-ppm NO2 Detection by Hybrid ZnO/QD Nanomaterials vs. Charge Localization in Core-Shell QD - Chizhov, Artem; Vasiliev, Roman; Rumyantseva, Marina; Krylov, Ivan; Drozdov, Konstantin; Batuk, Maria; Hadermann, Joke; Abakumov, Artem; Gaskov, Alexander (Frontiers in Materials, 2019)
New hybrid materials – photosensitized nanocomposites containing nanocrystal heterostructures with spatial charge separation, show high response for practically important sub-ppm level NO2 detection at room temperature. Nanocomposites ZnO/CdSe, ZnO/(CdS@CdSe), ZnO/(ZnSe@CdS) were obtained by the immobilization of nanocrystals – colloidal quantum dots (QDs), on the matrix of nanocrystalline ZnO. The formation of crystalline core-shell structure of QDs was confirmed by HAADF-STEM coupled with EELS mapping. Optical properties of photosensitizers have been investigated by optical absorption and luminescence spectroscopy combined with spectral dependences of photoconductivity, which proved different charge localization regimes. Photoelectrical and gas sensor properties of nanocomposites have been studied at room temperature under green light (λmax = 535 nm) illumination in the presence of 0.12 – 2 ppm NO2 in air. It has been demonstrated that sensitization with type II heterostructure ZnSe@CdS with staggered gap provides the rapid growth of effective photoresponse with the increase in the NO2 concentration in air and the highest sensor sensitivity toward NO2. We believe that the use of core-shell QDs with spatial charge separation opens new possibilities in the development of light-activated gas sensors working without thermal heating.